Investigation of beetroot (Beta Vulgaris) extracts compared to staurosporine in human breast cancer cells: cellular functions in-vitro study - Abushal, Suzan A.; Sami, Rokayya; Alqahtani, Nashi K.; Qahl, Safa H.; Harasani, Ahlam A.; Babteen, Nouf A.; Alharbi, Hend F.; Albalawi, Fahad Eid; Amer, Fatimah; Alfarteesh, Hajer A.; Alghamdi, Hayat A.; Almutairi, Sara M. (Frontiers in Oncology, 2026)
The cytotoxic and apoptotic effects of Beta Vulgaris (red beetroot) extracts prepared with various solvents, including water, EtOH (ethanol), MeOH (methanol), Ace (acetone), EtOAc (ethyl acetate), and BuOH (butanol), on staurosporine (Sts) in MCF-7 cells have been examined in the present study. The MTT assay showed that cell survival was significantly decreased in the treatment groups, with the extracts of BuOH (30.11%) and Ace (41.17%) showing the highest suppression in comparison to the control. A decrease in viable cells was verified by Trypan blue analysis; the viability of BuOH and Ace extracts was 48.41% and 52.45%, respectively. While cytochrome c release reached 11.08 ng/mL in BuOH-treated cells compared to 1.32 ng/mL in the control, caspase-3/7 activity increased dramatically, reaching 61.48% with BuOH and 53.72% with Ace. Reactive oxygen species (ROS) and hydrogen peroxide (H2O2) levels were high (62.71% and 5.11 µM, respectively), resulting in a 48.92% reduction in adenosine triphosphate (ATP). Annexin V-FITC/PI staining demonstrated that BuOH and Ace raised the values of early and late apoptosis by 26.19% and 29.47%, respectively. The BuOH extract had the strongest cytotoxic and pro-apoptotic effects across most assays, with the lowest survival rate (30.11%), high caspase-3/7 (61.48%), high cytochrome c release (11.08 ng/mL), strong ROS (62.71%), and H2O2 production (5.11 µM), and the highest early and late apoptosis rates (26.19% and 29.47%). The findings demonstrate the potential of Beta Vulgaris chemical compounds as natural anticancer agents against breast cancer cells.